Mobile health clinics in a rural setting: a cost analysis and time motion study of La Clínica in Oregon, United States - Abigail Higgins; Middy Tilghman; Tracy Kuo Lin (BMC Health Services Research)
Abstract Background Mobile Health Clinics (MHCs) are an alternate form of healthcare delivery that may ameliorate current rural–urban health disparities in chronic diseases and have downstream impacts on the health system by reducing costs. Evaluations of providers’ time allocation on MHCs are scarce, hindering knowledge transfer related to MHC implementation strategies. Methods Retrospective economic cost was assessed using business ledgers and expert assessments in 2023 US Dollar (USD) from 2022 to 2023. Time motion observational study assessed nurse practitioner (NP) and community health worker (CHW) time allocation and compared them between patients residing in isolated rural areas (hereafter isolated rural patients) and patients experiencing houselessness (PEH) sub-populations. Procedure codes were assessed retrospectively for each patient encounter (n = 1,981) over one year (April 2022 to April 2023). We used statistical significance tests (chi-square and Fisher’s Exact) to evaluate difference across sub-populations. Results Intervention start-up and operational costs totaled 275,000USD and 308,000USD, respectively, with the largest allocations to the modified recreational vehicle (RV) unit and labor. NP attributed 32% of time on direct care (mean = 153.00 min (SD = 37.80 min)), 38% on indirect care (186.0 (53.40)), and 21% on MHC tasks (104.00 (23.94)). CHW spent 47% of time on MHC tasks (182.00 (29.46)), 22% on medical care tasks (85.01 (SD 81.97)), and 22% on social needs tasks (87.70 (86.71 min)). NP time allocation did not differ significantly between isolated rural patients and PEH (p > 0.01), but CHW time did (p < 0.01). Of all procedures, 31.3% were vaccinations (N = 438), 27.0% were Covid-19 related (N = 377), 12.8% were outside referrals (N = 179), and 11.8% were point of care testing. Healthcare utilization varied between patient sub-populations, with Isolated Rural patient use dominated by Covid-19 and Influenza vaccines whereas PEH use was dominated by point of care testing (p < 0.01). Conclusion Patient sub-populations require varying provider time in different tasks and variable economic resources for interventions. As local policy makers balance resources and community health needs, a complete understanding of the resources required to operate an MHC and use of provider time is essential for informed decision making and successful implementation in underserved communities.